Routine and novel methods for isolation of extracellular vesicles - Popovic, Milica (Biologia Serbica, 2020)
Extracellular vesicles (EV) play an important role in many physiological and pathological processes. Three main classes of EV are recognized, based on their biogenesis: exosomes, microvesicles and apoptotic bodies. Exosomes are extracellular-vesicles of 30 to 150 nm found in many bodily fluids (blood, urine, milk, cerebrospinal fluid, etc.). Due to their cellular origin and role in physiological and pathological processes, exosomes present in body fluids are considered a unique source of non-invasive and clinically relevant biomarkers. Analysis of exosomes can provide insight into the state of the parent-cell from which they originated. However, there is great heterogeneity in the methodologies used for exosome purification affecting the results of downstream analysis. The most commonly used methods for purification are based on ultracentrifugation (UC), ultrafiltration (UF) and precipitation. However, these are hard to standardize, leading to confounding and misleading results during downstream analyses, especially when highly-sensitive techniques such as mass spectrometry are used. Furthermore, loss of certain fractions or damage of EVs can lead to loss in obtained protein and RNA profile. Consequently, there is an emerging need to obtain consensus protocols for exosome isolation and identification of specific sub-populations. This manuscript will critically review the most commonly used techniques for EV purification such as UC, UF, size-exclusion, precipitation and immunoaffinity (IA) methods. We will also review the use of nano-antibodies for the development of novel IA protocols and identification of new EV biomarkers.